"Maybe if I stop the drugs, then maybe they'd care?"-hospital care experiences of people who use drugs - Soo Chan Carusone; Adrian Guta; Samantha Robinson; Darrell H. Tan; Curtis Cooper; Bill O'Leary; Karen de Prinse; Grant Cobb; Ross Upshur; Carol Strike (BMC, 2019)
Abstract Background Drug use is associated with increased morbidity and mortality but people who use drugs experience significant barriers to care. Data are needed about the care experiences of people who use drugs to inform interventions and quality improvement initiatives. The objective of this study is to describe and characterize the experience of acute care for people who use drugs. Methods We conducted a qualitative descriptive study. We recruited people with a history of active drug use at the time of an admission to an acute care hospital, who were living with HIV or hepatitis C, in Toronto and Ottawa, Canada. Data were collected in 2014 and 2015 through semi-structured interviews, audio-recorded and transcribed, and analyzed thematically. Results Twenty-four adults (18 men, 6 women) participated. Participants predominantly recounted experiences of stigma and challenges accessing care. We present the identified themes in two overarching domains of interest: perceived effect of drug use on hospital care and impact of care experiences on future healthcare interactions. Participants described significant barriers to pain management, often resulting in inconsistent and inadequate pain management. They described various strategies to navigate access and receipt of healthcare from being "an easy patient" to self-advocacy. Negative experiences influenced their willingness to seek care, often resulting in delayed care seeking and targeting of certain hospitals. Conclusion Drug use was experienced as a barrier at all stages of hospital care. Interventions to decrease stigma and improve our consistency and approach to pain management are necessary to improve the quality of care and care experiences of those who use drugs.